The Effect Of Company Growth, Earnings Per Share, And Capital Structure On Dividend Policy With Company Age As A Control Variable - Annamali Lolo Ramma; Juniati Gunawan (Publikasi Indonesia, 2023)
This study aims to examine the effect of Company Growth, Earnings Per Share, and Capital Structure on Dividend Policy with Company Age as a control variable. This research was conducted using quantitative methods and the data used in this study were secondary data. The population of this study is trading and investment service companies listed on the Indonesia Stock Exchange for the period 2018 –2022. The sample selection was carried out by purposive sampling method so that research samples were obtained from as many as 34 companies with a total of 167 observations. Research sample data comes from the company's annual report, especially financial statements, and is processed using the SPSS application version 25. The results of hypothesis testing in this study show that Company Growth has a significant negative effect on Dividend Policy, Earnings Per Share has a significant positive effect on Dividend Policy, and Capital Structure has no effect on Dividend Policy.